PERKAWINAN BEDA AGAMA DALAM PRESPEKTIF HADITS - Lukman Hakim; Irwansyah; Wahyu Safitri (JURNAL CERDAS HUKUM, 2022)
The phenomenon of interfaith marriage in Indonesia today is increasingly difficult to contain. Because the District Court in Surabaya has given its blessing and legalized interfaith marriages. Indeed, this phenomenon occurs, but until now interfaith marriages continue to occur. Although previously the legislation regarding marriage already existed. Only the prohibition of interfaith marriage has not been determined explicitly. The prohibition of interfaith marriages is only contained in the Compilation of Islamic Law (KHI) articles 40 and 44. Unfortunately, these two articles were weakened by the government by giving legal legitimacy through the Supreme Court Decree Number: 1400 k/Pdt/1986. Apart from that, Islamic law also has a big role to play in examining interfaith marriage laws, because marriage cannot be separated from religious rules. Based on these problems. So the focus of this research is how interfaith marriages in the perspective of Hadith. This study uses library research methods (library research). If examined in the hadith, there is no textual hadith that prohibits interfaith marriages. It's just that there is one piece of hadith that substantially instructs the Ummah of the Prophet Muhammad to pay attention to the quality of prospective husbands and prospective wives. This proposition is correlated with the concept of sadd dzariah and fiqh rules which sound dar'ul mafasid maqoddamun alajalbil masolih. So interfaith marriage in the perspective of hadith, the law is haram.